Shifting Meaning of State Losses in BUMN Based on the Business Judgment Rule Principle - Fona Kartika Listiyapuji; Dyah Ochtorina Susanti; Firman Floranta Adonara (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2025)
State-owned enterprise faces complex business dynamics, including the risk of state losses due to managerial decisions. The Business Judgment Rule (BJR) principle serves as the basis for legal protection for the direction to make business decisions with professional freedom, as long as the decisions are made in good faith, with caution, and without conflict of interest. However, the application of this principle in Indonesia is still inconsistent, as seen from cases such as Pertamina and Merpati Nusantara Airlines which show heterogeneity in the assessment of the legal responsibility of directors. The focus of this study is: first, to find the meaning of state losses in the context of State-owned enterprise based on the BJR principle; and to formulate a concept so that the BJR doctrine is not misused. The study uses a normative juridical method (research law) with a doctrinal approach to examine changes in the meaning of state losses in State-owned enterprise based on the Business Judgement Rule.